Does the Enforcement of Labor Regulations Reduce Informality? The Case of Peru - Pinto, María Florencia (2026)
This article examines the effects of strengthened labor regulation enforcement on labor market outcomes in Peru from 2010 to 2019. In 2013, the Peruvian government established a national labor inspection agency, which was progressively rolled out nationwide. This reform led to a substantial increase in the frequency and severity of fines imposed on formal firms. Despite this heightened enforcement, our analysis using extended two-way fixed effects models finds no significant effects on overall employment levels. Moreover, there is no evidence of changes along either the intensive margin—informal employment within formal firms—or the extensive margin—the share of employment in informal firms. These findings suggest that increased enforcement of labor regulations did not lead to measurable shifts in labor informality or employment outcomes during this period.